An Examination of the Implementation of Mathematics Lessons in a Chinese Kindergarten Classroom in the Setting of Standards Reform. Issue 1 (2nd January 2017) - Hu, Bi Ying; Quebec Fuentes, Sarah; Ma, Jingjing; Ye, Feiwei; Roberts, Sherron Killingsworth
ABSTRACT: In China, the 2001 Kindergarten Education Guidelines (Trial), or New Outline, delineates what constitutes high-quality, developmentally appropriate practices in all early childhood education curriculum domains, including mathematics. The New Outline is known for advocating a child-centered, play-based approach to teaching and learning, a significant change from teacher-directed instruction. Research highlights a gap between the intended practices set forth in the New Outline and the enacted practices in Chinese kindergarten classrooms. This descriptive study examines the implementation of 10 mathematics lessons, delivered over a 6-month period, from one Chinese kindergarten classroom in light of the New Outline . The analysis revealed that the lessons reflected aspects of the New Outline . However, overall, the lessons lacked critical components to provide students with opportunities to construct an understanding of the mathematics and become independent learners in five areas: (1) opportunities to inspire autonomous and life-long learning, (2) strategies for differentiated instruction, (3) use of resources to represent mathematics concepts, (4) student-centered instructional approaches, and (5) ways to foster communication.